2002
DOI: 10.1088/0031-9155/47/12/305
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of selected native and coagulated human brain tissues in vitro in the visible and near infrared spectral range

Abstract: Medical laser applications require knowledge about the optical properties of target tissue. In this study, the optical properties of selected native and coagulated human brain structures were determined in vitro in the spectral range between 360 and 1100 nm. The tissues investigated included white brain matter, grey brain matter, cerebellum and brainstem tissues (pons, thalamus). In addition, the optical properties of two human tumours (meningioma, astrocytoma WHO grade II) were determined. Diffuse reflectance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
480
3
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 573 publications
(522 citation statements)
references
References 28 publications
37
480
3
2
Order By: Relevance
“…Previous studies, which used perfused brain preparations or synthetic brain tissue phantoms (53), underestimated tissue absorption for 200-600 nm (blue and green) light propagation. Specifically, we report absorption coefficients two-to threefold larger than the largest reported in a recent study of fresh and frozen brain slices (30) and about 10-fold larger than the values that Yaroslavsky et al (29) reported based on measurements taken in postmortem human tissue. Unfortunately, the ex vivo values of Yaroslavsky et al (29) have been used widely in the optogenetics literature (26,28,53,(74)(75)(76)(77)(78) because, before the present study, techniques were not available for in vivo measurements of light propagation in living brain tissue across the full spectrum of visible light.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Previous studies, which used perfused brain preparations or synthetic brain tissue phantoms (53), underestimated tissue absorption for 200-600 nm (blue and green) light propagation. Specifically, we report absorption coefficients two-to threefold larger than the largest reported in a recent study of fresh and frozen brain slices (30) and about 10-fold larger than the values that Yaroslavsky et al (29) reported based on measurements taken in postmortem human tissue. Unfortunately, the ex vivo values of Yaroslavsky et al (29) have been used widely in the optogenetics literature (26,28,53,(74)(75)(76)(77)(78) because, before the present study, techniques were not available for in vivo measurements of light propagation in living brain tissue across the full spectrum of visible light.…”
Section: Discussioncontrasting
confidence: 67%
“…To compare visible light wavelengths accurately, and thus select the optimal opsin for our studies, we developed techniques to measure visible light propagation omnidirectionally in vivo. Previous optogenetic studies have used visible light propagation measurements and tissue properties derived from in vitro or ex vivo specimens (26)(27)(28)(29)(30)(31)(32). For example, Azimipour et al (33) recently published an atlas of optical properties and predicted light distribution in rat brain tissue.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…isolated tumor cell nests in the infiltration zone of the lesion), ray tracing simulations were performed using the Monte Carlo-based software TracePro (Lambda Research Corporation, Littleton, MA, USA). A tumor cube (fluorescent cube with optical properties of brain tumor taken from [36] and a constant PpIX concentration of 2 µM) with variable edge length between 0.04 mm and 15 mm (the latter one considered infinitely large as compared to fiber diameter and light penetration depth) was embedded in a brain cube (non-fluorescent cube with optical properties of gray matter compiled from [36], [37] and [45]) with an edge length of 30 mm. As the simulation was intended to mimic the experimental setup, one surface of the tumor cube was in contact with the excitation/detection fiber (core diameter 200 µm, NA = 0.22).…”
Section: Ray Tracing Simulations With Variable Tumor Sizementioning
confidence: 99%
“…In spite of all the success of DOT in cancer diagnosis applications, to date, only absorption (µ a ) and reduced scattering (µ s ) coefficients reconstruction can be found in the literature. However, the anisotropy factor g of the Henyey-Greenstein (H-G) phase function has an important effect on light propagation [6] and can reveal rich informations on the anisotropic scattering behavior of the tissue: [7] showed that the g value of porcine brain tissue increases from 0.561 to 0.834 after thermal coagulation, [8] demonstrated that the anisotropy factor g of rat liver decreases from 0.952 to 0.946 in a tumor at 633 nm, [9] proved experimentally that g was different for normal human liver tissue and liver metastases at three different wavelengths. That means that g can also be modified when tissue is affected by an eventual tumor besides µ a and µ s .…”
Section: Introductionmentioning
confidence: 99%